Personnel selection : a self instructional program - McKenna, Frank S.; Perloff, Robert O. (Chicago : Educational Methods, 1967)
This book reveals some of the basic rules and principles in personnel selection for capacity building.
asm 24/01/2019
Loans
Keywords: Employee selection; Employees--Recruiting